Gamified Interventions for Promoting the Psychosocial Well-Being of School-Aged Children : A Scoping Review - Kubota, Kaile (Mary Ann Liebert, 2025)
Gamified health interventions can offer child-centered and tailored health-promoting strategies. Evidence suggests that its various mechanics foster engagement that can be utilized to promote health and well-being and influence health behavior. At present, psychosocial challenges among school-aged children are becoming a global predicament. We conducted a scoping review to explore the range and nature of evidence on gamified interventions for promoting the psychosocial well-being of school-aged children from the general population. We followed the Arksey and O'Malley framework and extracted sources of evidence from five databases. Our review findings were summarized with basic numerical analysis and provided with narrative accounts based on a gamification taxonomy and the Template for Intervention Description and Replication (TIDieR). We identified 12 gamified interventions and included 23 records that reported their development and evaluation. Theories on emotions, behaviors, social skills, and mental health were commonly applied frameworks. Narrative was found as the most commonly used gamification mechanic (11/12, 91.7%), followed by avatar and tasks (10/12, 83.3%), feedback system and level progression (9/12, 75%), points (7/12, 58.3%), badges (5/12, 41.7%), progress bar (4/12, 33.3%), and virtual goods, reminders, and time pressure (2/12, 16.7%). The included sources of evidence reported significant improvements in some of the measured psychosocial outcomes; however, studies on this domain for this particular target group are still considerably limited. Further research is needed to determine how the applied theories and gamification mechanics brought about the change in psychosocial outcomes, bridging the gap in current evidence.